A new species of Astropecten (Echinodermata: Asteroidea: Paxillosida: Astropectinidae) and a comparison of the Astropecten species from the Gulf of Mexico and the East Florida Shelf - Cobb, Janessa C.; Lawrence, John M.; Herrera, Joan C.; Janies, Daniel (Zootaxa, 2019)
A new species of Astropecten is described, supported by morphological and molecular evidence, from the Gulf of Mexico and the East Florida Shelf with most specimens from 30–60 m in depth. The new species, A. mcedwardi n. sp., is small, with a maximum major radius < 30 mm. Specimens of A. mcedwardi n. sp. have been found in five museums as an undescribed species or misidentified under several names. The spination of the oral surface most closely resembles that of Astropecten antillensis Lütken, 1859 from the Caribbean, but the body form is similar to that of Astropecten duplicatus Gray, 1840, which is found in the same geographic range. Examination of specimens from different collections indicates that the new species may overlap in distribution with A. antillensis along the East Florida Shelf. Sequencing and phylogenetic analysis of two mitochondrial genes reveal that A. mcedwardi is closely related to A. antillensis but that its phylogenetic lineage is distinct from that of A. antillensis.